Secondary Structure Modulation of Triptycene-Based One-Handed Helical Ladder Polymers through π-Extension of Achiral Segments - Ikai, Tomoyuki; Tanaka, Atsuya; Shiotani, Takumi; Oki, Kosuke; Yashima, Eiji (Organic Materials, 2023)
A series of enantiopure triptycene-based one-handed helical ladder polymers containing π-extended achiral segments with naphthalene, fluorene, and carbazole spacers was synthesized through quantitative and chemoselective ladderization of the corresponding precursor polymers with random-coil conformations. The helical handedness (right- or left-handed) and geometry (loose coil or ribbon) of the resulting ladder polymers were readily modulated by tuning the structure of the achiral spacers despite the incorporation of the same point chirality of the triptycene unit. All the helical secondary structures are stable and robust due to the shape-persistent ladder structures, showing the characteristic and environment-independent chiroptical properties.
Keywords: alkyne benzannulations; chirality; helical polymers; ladder formation; secondary structures; π-extension